2021
DOI: 10.1002/nau.24646
|View full text |Cite
|
Sign up to set email alerts
|

Artificial urinary sphincter or a second adjustable transobturator male system offer equivalent outcomes in patients whom required revision on the initial ATOMS device: An international multi‐institutional experience

Abstract: Aim: To evaluate treatment options after surgical revision of adjustable transobturator male system (ATOMS) and the results of further incontinence implantation. Materials and Methods: A retrospective multicenter study evaluating patients with surgical revision of ATOMS in academic institutions. Causes and factors affecting revision-free interval were studied and also the frequency of device explant and placement of second ATOMS or artificial urinary sphincter (AUS) at surgeon discretion. Operative results, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 33 publications
1
20
0
Order By: Relevance
“…Other studies specifically focus on complications and device durability. The largest study involves 902 patients from Europe and Canada and is dedicated to rescue surgery after failed ATOMS implant [ 32 ]. In summary, the body of evidence regarding the mode of action, surgical technique and operative and postoperative results, including not only efficacy and safety but also patient-reported outcomes (PRO) and satisfaction with the device, has been increasing in the past decade.…”
Section: Atoms Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies specifically focus on complications and device durability. The largest study involves 902 patients from Europe and Canada and is dedicated to rescue surgery after failed ATOMS implant [ 32 ]. In summary, the body of evidence regarding the mode of action, surgical technique and operative and postoperative results, including not only efficacy and safety but also patient-reported outcomes (PRO) and satisfaction with the device, has been increasing in the past decade.…”
Section: Atoms Resultsmentioning
confidence: 99%
“…The percent of explant rate ranged between 0–19%, depending mainly on the length of follow-up and in different patterns of rescue treatment proposed. A multicenter study with a large number of patients revealed an 8.3% explant rate after 4 years of follow-up, and the main reasons were persistent bothersome incontinence and scrotal erosion at the port site [ 32 ]. Another study exclusively focused on surgical complications and revealed they presented more frequently in the population of patients with previous radiotherapy ( p = 0.003) and in patients with previous surgery for urethral stricture ( p = 0.017) [ 36 ].…”
Section: Atoms Resultsmentioning
confidence: 99%
“…On the other hand, although ATOMS placement does not anatomically dissect the bulbar urethra circumferentially or separates the bulbospongiosus muscle, some risk of devascularization or atrophy caused by sustained compression remains. In this regard, cases requiring late surgical revision have shown that ATOMS caused less urethral atrophy than AUS [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…ATOMS provides an efficient alternative for both the first- and second-line treatments after other failed options [ 4 , 5 , 6 , 7 ]. This device is placed using a trans-obturator passage and positioned under the urethra in order to achieve ventral compression of the bulbar urethra ventrally.…”
Section: Introductionmentioning
confidence: 99%
“…Despite complications that may occur and possible pain after the implantation, which can hamper results in terms of patient satisfaction, overall satisfaction with the device remains very high [3,12,13]. Long-term outcomes appear reassuring as well [14], though a proportion of patients undergo device explantation for several reasons that include ineffectiveness, port erosion, and device infection [15,16].…”
Section: Discussionmentioning
confidence: 99%